4D strategies for lung tumors treated with hypofractionated scanning proton beam therapy: Dosimetric impact and robustness to interplay effects. (May 2020) - Mastella, Edoardo; Molinelli, Silvia; Pella, Andrea; Vai, Alessandro; Maestri, Davide; Vitolo, Viviana; Baroni, Guido; Valvo, Francesca; Ciocca, Mario
Highlights: Two 4D strategies were investigated to mitigate interplay in PBS proton therapy. 4D plans were robustly optimized for hypofractionated treatments of lung tumors. Delivery accuracy and interplay were evaluated on a heterogeneous moving phantom. Restricted 4D robust optimization combined with gating was highly robust to motion. Interplay became more severe with increasing amplitude for ungated plans. Abstract: Purpose: To investigate the impact of four-dimensional robust optimization (4DRO) on dose delivered to lung cancer patients in pencil beam scanning proton therapy. Methods and materials: 2 strategies were compared for 20 lung cancer patients, using a different number of breathing phases of the reconstructed 4D computed tomography (CT) included in the plan optimization problem. In the restricted approach combined with gating, only 3 phases close to reference end-exhale were considered instead of the whole breathing cycle. The prescribed dose was 60 Gy(RBE) in 10 fractions. Target coverage (D98%) and dose to healthy tissues were evaluated using Wilcoxon signed-rank test. To assess the robustness against interfractional anatomical and respiratory variations, the optimized plans were recalculated on re-evaluation 4DCTs. To compare the sensitivity of both strategies to interplay effects, we implemented an end-to-end test with a home-made heterogeneous moving phantom and ionization chambers measurements. Robustly optimized plans with prescription doses of 6 Gy(RBE) were delivered in different dynamic conditions. Results: Both 4D robustly optimized plans reached the same target coverage ( p  = 0.56), while a statistically significant decrease of the homolateral lung dose was observed using the restricted approach ( p  < 0.0001). Plan recalculations within 15 days from the treatment simulation showed the same robustness of target D98% against interfractional variations ( p  = 0.48), with an average decrease of approximately 3 Gy(RBE). Phantom measurements confirmed the delivery accuracy of the restricted approach (mean dose deviations <5%). Higher deviations were found for ungated full 4DRO and larger motion amplitude. Conclusion: The restricted approach combined with gating improved normal tissue sparing and was shown to be more robust to single fraction deliveries and large motion amplitude.